Analyzing of implementation maternal audit program in community health center: a qualitative study - Atiyah, Fityah U.; Sundari, Sri; Rosa, Elsye M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Maternal audits are part of quality control that is routinely carried out and aims as an essential learning material in evaluating maternal services in an area so that the expected outcome is a decrease in maternal mortality in an area. The maternal audit program that is carried out will undoubtedly benefit health facilities that provide services in the maternal sector, such as primary, secondary, and tertiary health facilities. Methods: This study used a qualitative case study method with a purposive sampling technique. The data collection technique was carried out by interviewed using the in-depth interview method, and triangulation was carried out using observation and document review. Results: The community health center has contributed to implementing maternal audits, starting from the data collection process, participating in district audit forums, and implementing the recommendations. Four factors influence the implementation of the maternal audit program at the community health center in reducing maternal mortality, namely the knowledge of health workers, the involvement of health workers in the community health center in the audit process, the recommendations for the results of the audit process and the implementation of follow-up on the results of the audit recommendations at the community health center. Conclusions: The maternal audit program can reduce maternal mortality and improve the maternal and child service system at the community health center level, although there are still several obstacles in implementing the recommendations of the audit results.